An insight into the growth and nutritional requirements for ligninolytic enzymes production by Rigidoporus vinctus - Shehnaz,; Prasher, I B (Journal of Postharvest Technology, 2022)
Rigidoporus vinctus (Berk. and Ryverdan) is a white-rot fungi that belongs to the Agaricomycete class of division Basidiomycota. It produces the  ligninolytic enzymes having many biotechnological applications such as the degradation of xenobiotic compounds and dyes. It is also used in inducing  agarwood formation and another application of this fungi is that it produces oil/lipids so it can also be used as biofuel. The study was carried out to  examine the in vitro growth and ligninolytic enzymes production by the fungus. The growth of fungi was examined with different physical parameters  (pH, temperature and days of incubation), in contrast the growth and ligninolytic enzymes activity was examined with respect to different carbon and  nitrogen sources. The optimum growth of fungi was observed with Richard’s medium at 32°C and with initial pH of 6.0 on 24th day of incubation.  Starch is the best carbon source for growth, whereas LiP and MnP activity both were maximum expressed in maltose and laccase activity was  maximum in glucose supplemented media. In the case of inorganic nitrogen compounds, Rigidoporus vinctus attained optimum growth with  ammonium sulphate and maximum activity for LiP, MnP and laccase were observed with ammonium chloride, ammonium sulphate and ammonium  oxalate supplemented media, respectively. In the case of organic nitrogen sources fungi expressed optimum growth with L-proline, whereas LiP, MnP  and laccase activity were maximum in DL-tryptophan, DL-valine and DL-aspartic acid supplemented media, respectively.
Keywords: Agaricomycete; ligninolytic enzymes,; Rigidoporus vinctus; white rot